Analisa Perbandingan Strategi Visual Iklan Brand Marketplace Bukalapak dan Tokopedia - Azdin Akbar (Bina Nusantara University, 2020)
In the social media era that has become part of life of today's society makes buying and selling activity through online media also become a commonplace. People are getting more comfortable making transactions through online media. The rise of online marketplace that sprung became an evidence that many people nowadays have no doubt selling or shopping on the internet. This research aims to study the visual strategy of BukaLapak and Tokopedia advertising campaigns. This study used the method of content analysis by collecting uploaded BukaLapak and Tokopedia video ads in their social media, especially Youtube channel. This study analyzes the visual strategies applied by BukaLapak and Tokopedia. The data collected are in the form of visual advertising campaign within the specified period of time. This research is expected to show how is the correlation between visual strategy used and its impact on user engagement on BukaLapak and Tokopedia Youtube channel.